(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The main factors influencing the durability and performance of agricultural machinery are their mechanical wear, the action of various types of corrosion, and their combination. The fight against corrosion in agricultural machinery is not only a technical but also an economic problem, which can be solved by selecting chemically resistant anti-corrosion paints and varnishes that most fully satisfy the specific operating conditions of agricultural machinery.